Still focused on public deficits. Some remarks on the euro area stability programmes 2012-2015 - Gregor Semieniuk (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
Using the financial balances accounting identity, we analyze whether there is evidence in recent national accounting data and the projections of the Stability Programmes (SP), that the focus on fiscal deficits to the exclusion of other economic variables risks further deterioration of the euro area economy's growth rate. We find that, in the past given the focus on shrinking public deficits, growth forecasts have almost always deteriorated from one SP to the next, while the macroeconomic situation is not markedly different from the beginning of the euro area crisis, 2010. We conclude that continued fiscal austerity and disregard of current account imbalances is likely to lead to further deteriorating data that fail to live up to current growth forecasts. This will lead in turn to further growth forecast downward revision in the next SP batch. A simple simulation of a deterioration in the external economic environment indicates that a symmetric rebalancing of the current account imbalances might be more feasible than the current, asymmetric rebalancing.
urn:nbn:de:101:1-201211143732
Keywords: E21; E22; E23; E44; E50; 330; Euro area crisis; fiscal deficit; financial balances accounting identities; macroeconomics imbalances; austerity; stability programmes